Molecular Identification of Yeast Candida glabrata from Candidemia Patients in Iraq - Risan , Mohsen H. (Iraqi Journal of Science, 2022)
This study aimed for isolation and identification of Candida glabrata from specimens of blood collected from national center of hematology /Al - mustansiriya University of immunocompromised patients infection of candidemia after diagnosis by doctor. Results showed the morphological features on many media SDA and Corn meal and differential CHROMagar. Colonies appear small and pink pale to dark. Microscopic exam of show that C. glabrata not form pseudohyphae and not produce germ tubes, the cell size 2 - 3 microns, on the other hand, Biochemical test of C. glabrata have high ability for fermentation of glucose within three hours and trehalose given false positive within two hrs., and the Urease test given negative result, on the other hand , The results indicated that the DNA of isolated strains was extracted successfully. The results of PCR amplification which was performed on that DNA extracted from all isolates were confirmed by the electrophoresis analysis. The primer amplified of the ribosomal DNA in all strains tested, resulting in amplified products of approximately 610 bp in C. glabrata.